Evaluation of Physical Education, Sports, and Health Learning Through a Goal-Free Approach to Reveal Unexpected Outcomes - Muhammad Ashfal Ashfiya'; ME Winarno (CV. SAMODRA INSAN PENA, 2026)
Evaluation of learning is generally focused on the achievement of predetermined objectives, which may overlook various impacts that emerge naturally during the learning process, particularly in Physical Education, Sports, and Health (PJOK), which is holistic in nature. This study aims to reveal the unexpected outcomes of PJOK learning using the Goal-Free Evaluation (GFE) approach. This study employed a qualitative evaluative case study design involving six student leaders from grades VII–IX, selected purposively. Data were collected through semi-structured interviews and analyzed using inductive thematic analysis. The findings identified five major unexpected outcomes of PJOK learning. Discipline and responsibility emerged as the most dominant theme, reported by all participants, while leadership, social interaction, and negative emotional experiences were identified by the majority of informants. Problem-solving skills also emerged as an additional outcome, although less frequently reported. These results indicate that PJOK learning produces a wide range of affective, social, and cognitive impacts beyond formal learning objectives. This study highlights the importance of using a Goal-Free Evaluation approach to capture both positive and negative learning outcomes more comprehensively. The findings contribute to strengthening the evaluation paradigm in PJOK by emphasizing authentic learning impacts that are often overlooked in goal-based evaluations.